1999
DOI: 10.1523/jneurosci.19-13-05348.1999
|View full text |Cite
|
Sign up to set email alerts
|

TheCaenorhabditis elegans unc-49Locus Encodes Multiple Subunits of a Heteromultimeric GABA Receptor

Abstract: Ionotropic GABA receptors generally require the products of three subunit genes. By contrast, the GABA receptor needed for locomotion in Caenorhabditis elegans requires only the unc-49 gene. We cloned unc-49 and demonstrated that it possesses an unusual overlapping gene structure. unc-49 contains a single copy of a GABA receptor N terminus, followed by three tandem copies of a GABA receptor C terminus. Using a single promoter, unc-49 generates three distinct GABAA receptor-like subunits by splicing the N termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
233
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(249 citation statements)
references
References 29 publications
14
233
2
Order By: Relevance
“…2, A-C). Interestingly, when this was repeated in mutants lacking the sole postsynaptic ionotropic GABA A receptor UNC-49 (Bamber et al 1999), the elongation effects were not completely abolished but worms still elongated by up to 2% (Figs. 1, A and B, and 2, A-C; Supplemen- Fig.…”
Section: Gbb-1/2 Receptors Contribute To Gaba Effects At the Nmjmentioning
confidence: 93%
“…2, A-C). Interestingly, when this was repeated in mutants lacking the sole postsynaptic ionotropic GABA A receptor UNC-49 (Bamber et al 1999), the elongation effects were not completely abolished but worms still elongated by up to 2% (Figs. 1, A and B, and 2, A-C; Supplemen- Fig.…”
Section: Gbb-1/2 Receptors Contribute To Gaba Effects At the Nmjmentioning
confidence: 93%
“…In UNC-49B-GFP (green fluorescent protein), GFP is inserted in frame in the M3-M4 cytoplasmic loop of the UNC-49B subunit in a genomic fragment that contains all three GABA receptor subunit open reading frames plus 400 nt of the unc-49 promoter (Bamber et al, 1999). In this construct, we replaced GFP with YFP (yellow fluorescent protein) to generate pJL41.…”
Section: Methodsmentioning
confidence: 99%
“…Transformation was performed by microinjection of plasmid DNA into the gonad (Mello et al, 1991). unc-49(e407);lin-15(n765ts) worms were injected with a DNA mixture containing pJL37 (Punc-47::snb-1-CFP) (20 ng/ l), a gel-purified AflIIMluI fragment of pJL41 (unc-49B-YFP missing the 5Ј end of the gene) (20 ng/ l) and a 110/38 unc-49 PCR fragment (10 ng/ l) containing a 4 kb promoter fragment plus 2 kb of the 5Ј coding sequence, as described by Bamber et al (1999). pEKL15, a plasmid that contains the wild-type lin-15 gene (Clark et al, 1994), was coinjected at 40 ng/ l as a cotransformation marker.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 26 C. elegans GABAergic cells modulate locomotion (DD and VD motor neurons), foraging (RMEs), and defecation (AVL and DVB) behaviors (McIntire et al, 1993b;Schuske et al, 2004). Mutations in the GABA biosynthetic enzyme glutamic acid decarboxylase (GAD) (unc-25;Jin et al, 1999), vesicular transporter (unc-47;McIntire et al, 1997), and excitatory and inhibitory receptors (exp-1; Beg and Jorgensen, 2003;unc-49;Bamber et al, 1999), have been described in detail. In addition, earlier studies had demonstrated uptake of exogenous GABA into a subset of C. elegans neurons (McIntire et al, 1993b).…”
Section: Introductionmentioning
confidence: 99%